Animated Video Approaching Contextual Learning in Natural Science Subject Class VII - Sumampan, Nyoman Sukma; Sudarma , I Komang; Simamora , Alexander Hamonangan (LPPM Undiksha, 2022)
In the era of technological, the readiness of teachers to educate their participants through online learning is very important. Animated video is one way of teaching that can help students in improving student learning outcomes. This study aimed to analyses the process of developing and validating animated videos with a contextual learning approach in natural science subjects for class VII at Junior High School. This research is development research using the ADDIE model. The subjects of this study were content experts, design experts, media experts, three students in individual trials, and nine students as small group trials. The data collection methods used are observation, interviews, document recording, and questionnaires. The data analysis technique used descriptive qualitative and quantitative analysis techniques. The result of this study found that learning content expert test results were 94%, the instructional design expert test was 91.66%, the learning media expert test was 97.17%, the individual trial was 91.33%, and the small group trial was 94.66% with the overall score percentage. Very well qualified. The implication of this research is to make students more active in learning, create a more fun learning atmosphere, be more independent, and understand learning material by connecting it to everyday life.